From here to there : a first book of maps - French, Vivian (Candlewick Press, 2023)
One day, Anna's friend Zane sends her an invitation to come over to play, and inside the envelope is a map. But Anna is convinced the map can't be right--why has Zane put his house in the middle and hers on the edge? So Anna decides to draw a map of her own, and Dad joins in as well. With an inviting narrative, child-friendly illustrations, and running commentary about various aspects of maps, aspiring cartographers are introduced to everything from symbols to point of view, road maps to family trees--and even a special "cat map" of Anna's pet's favorite spots. A final spread spurs readers to try their own hand at mapmaking.